A NOVEL TASTING PLATFORM FOR SENSORY ANALYSIS OF SPECIALTY COFFEE - Gutiérrez-Guzmán, Nelson; Cortés-Cabezas, Albeiro; Chambers IV, Edgar (Coffee Science - ISSN 1984-3909, 2018)
Although there are many good tools to evaluate coffee, such as rigorous cupping protocols, all of them require improvements in order to benefit scientific research. One aspect to highlight is that coffee is a very important product worldwide and has been and is being investigated for its complexity. All research and any improvement in crop or processing ends-up being verified in the coffee cup quality, which is accomplished through the cupping procedures. However, sufficient tools have not been designed in order to manage the cupping procedures, in accordance with the technological level we have available now. Basically, sheets of paper are used to manage the cupping scores, which hinder the subsequent analysis process, making hard to know what happens inside coffee beans with greater precision and thoroughness. Another worrying aspect is that each region, at each country uses a different format with different flavor references to carry out the scoring, which has generated problems of unity of criteria on the analysis and this is not good to the coffee business. This paper presents the design of a web platform to make information storage and results processing of cupping procedures of specialty coffees easier. The main objective is to achieve better managing of the cupping model for the sensory analysis using a digital environment, allowing greater agility in the treatment of results and a more organized management of the information of the specialty coffees.